Additional studies in Neobertiera (Rubiaceae, Sipaneeae): a new species from the state of Pará, Brazilian Amazon, and a new combination for a species from French Guiana - Delprete, Piero G. (Phytotaxa, 2019)
In a recent revision of Neobertiera, three new species were described and the distylous condition of this genus was reported for the first time. In the present paper, a new species, N. montedouradensis, from the state of Pará, Amazon Basin, is described, which represents a significant range extension and the first record of this genus for Brazil. This new species is unique within the genus by having hypanthia and fruits with trichomes conspicuously tuberculate at base. In addition, a new combination is proposed for a species from French Guiana recently named N. glomerata. A correction regarding the corolla size of N. pakaraimensis is included. In view of these taxonomic novelties, a key to the five species of Neobertiera is provided.